Optimal duration of DAPT after second-generation drug-eluting stent in acute coronary syndrome. - Ji-Yong Jang (PLoS ONE, 2018)
BACKGROUND:We evaluated optimal duration of dual antiplatelet therapy (DAPT) after second-generation drug-eluting stent (DES) implantation in acute coronary syndrome (ACS). MATERIAL AND METHODS:From pooled analysis of three randomized clinical trials (EXCELLENT, IVUS-XPL, RESET), a total of 2,216 patient with ACS undergoing second-generation DES implantation were selected. Each study randomized patients to a short-duration DAPT arm (n = 1119; ≤6 months) or a standard-duration DAPT arm (n = 1097; ≥12 months). Two-thirds of patients were male, and their mean age was 63 years. Mean DAPT durations were 164 ±76 and 359 ±68 days, respectively. The primary endpoint was composite of cardiac death, myocardial infarction, stent thrombosis, stroke or major bleeding during the first 12 months after implantation, analyzed according to the intention-to-treat population. RESULTS:Demographic characteristics were balanced between groups. Mean DAPT duration was 164 and 359 days, respectively. Primary endpoint occurred in 22 patients with short-DAPT and 21 patients with standard-DAPT (2.0% versus 1.9%; hazard ratio [HR] 1.03; 95% confidence interval [CI] 0.56-1.86; p = 0.94). Landmark analysis after six-months, no significant difference in primary endpoint between short and standard duration DAPT (1.0% versus 0.8%; HR 1.22; 95% CI 0.51-2.95; p = 0.66). CONCLUSIONS:Short-duration DAPT (≤6 months) demonstrated a similar incidence of net adverse cardiovascular and clinical events at 12 months after second-generation DES in ACS compared with standard duration DAPT (≥12 months). CLINICAL TRIAL REGISTRATION:EXCELLENT (ClinicalTrials.gov, NCT00698607), RESET (ClinicalTrials.gov, NCT01145079), IVUS-XPL (ClinicalTrials.gov, NCT01308281).